Konflik Pertanahan Perkebunan Sawit di Daerah Aliran Sungai: Kasus DAS Siak, 2009-2014 - Isril; Khairul Anwar; Auradian Marta (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
The focus of this research is to find the law political model on the conflict situation in case DAS Siak years 2009-2014. This focus of this research is to find the factor influence of the conflict land DAS Siak from the law perspective. Method of this research is to identify; (1) the law factor and; (2) the non-factor conflict law by Berhard Limbong concept,and (3) the indentify structural factor. The result of this second years study is about the law model of land the Siak riverside area. And the good goverment and the DAS society value.